Rhes depletion promotes striatal accumulation and aggregation of mutant huntingtin in a presymptomatic HD mouse model - Pan, Yongcheng; Tang, Beisha; Li, Xiao-Jiang; Li, Shihua; Liu, Qiong (Frontiers in Aging Neuroscience, 2023)
Introduction Huntington’s disease (HD) is caused by CAG trinucleotide repeats in the HTT gene. Selective neurodegeneration in the striatum is prominent in HD, despite widespread expression of mutant HTT (mHTT). Ras homolog enriched in the striatum (Rhes) is a GTP-binding protein enriched in the striatum, involved in dopamine-related behaviors and autophagy regulation. Growing evidence suggests Rhes plays a critical role in the selective striatal degeneration in HD, but its specific function in this context remains complex and controversial. Methods In this study, we utilized CRISPR/Cas9 to knockdown Rhes at different disease stages through adeno-associated virus (AAV) transduction in HD knock-in (KI) mice. Immunoblotting and immunofluorescence were employed to assess the impact of Rhes depletion on mHTT levels, neuronal loss, astrogliosis and autophagy activity. Results Rhes depletion in 22-week-old HD KI mice (representing the presymptomatic stage) led to mHTT accumulation, reduced neuronal cell staining, and increased astrogliosis. However, no such effects were observed in 36-week-old HD KI mice (representing the symptomatic stage). Additionally, Rhes deletion in 22-week-old HD KI mice resulted in increased P62 levels, reduced LC3-II levels, and unchanged phosphorylation of mTOR and beclin-1, unchanged mTOR protein level, except for a decrease in beclin-1. Discussion Our findings suggest that knockdown Rhes promotes striatal aggregation of mutant huntingtin by reducing autophagy activity in a mTOR-independent manner. Rhes plays a protective role during the presymptomatic stage of HD KI mice.